Overview of the geology and related hazards of the Ararat depression - Avagyan , Ara; Arakelyan , Dmitri; Avagyan , Seda; Sahakyan , Lilit; Haroutiunian , Rouben; Egnatosyan , Naira; Alaverdyan , Gagik; Asatryan , Armen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This paper presents an overview of the geology, structure and related hazards of the Ararat Depression. The Cenozoic intermountain depression is located to the south of the Lesser Caucasus and formed after the Late Cretaceous-Paleogene closure of the Tethys Ocean and the start of Arabia-Eurasia collision. At the base of the Ararat Depression lies a thick sequence of Neoproterozoic crystalline basement (borehole data), Paleozoic sedimentary, Mesozoic ophiolitic, including Upper Cretaceous sedimentary and Cenozoic sedimentary, volcanisedimentary, volcanic deposits. The depression is formed as a result of tectonic activity mainly controlled by oblique-slip reverse and thrust segmented faults activated in post Oligocene-Miocene times. These compressional faults resulted in the formation of segmented asymmetric folds and fault structures. The integration of various natural phenomena is characteristic of the Ararat Depression, which is significant. The Ararat Depression is an area highly influenced by geological hazards․ Only the 1840 event shows a catastrophic natural disaster that involved multiple hazards interacting with each other, resulting in significant damage and loss of life. The hazards included an earthquake, volcanic eruption, lahars, debris flow, landslides, floods caused by river dams, ground subsidence, river migration and liquefaction. Understanding the geological processes and hazards in the Ararat Depression is essential for assessing and mitigating the risks associated, which influence and have an impact on human activities.